Association Between Cholinesterase Inhibitors and New-Onset Heart Failure in Patients With Alzheimer's Disease: A Nationwide Propensity Score Matching Study - Hsieh, Ming-Jer; Chen, Dong-Yi; Lee, Cheng-Hung; Wu, Chia-Ling; Chen, Ying-Jen; Huang, Yu-Tung; Chang, Shang-Hung (Frontiers in Cardiovascular Medicine, 2022)
Background: Autonomic nervous dysfunction is a shared clinical feature in Alzheimer disease (AD) and heart failure (HF). Cholinesterase inhibitors (ChEIs) are widely used autonomic modulators in patients with AD, but their primary preventive benefit on new-onset HF is still uncertain. Objective: This study examined whether ChEIs have a primary preventive effect on new-onset HF in patients with AD. Methods: This propensity score matching (PSM) study was conducted using data from the National Health Insurance Research Database of Taiwan for 2001 to 2017. Certificated patients with AD and without a history of HF were divided into ChEI (donepezil, rivastigmine, or galantamine) users or nonusers. The primary endpoint was new-onset HF, and the secondary endpoints were myocardial infarction and cardiovascular death after 10-year follow-up. The Cox proportional hazards model was used to estimate the treatment effects on clinical outcomes. Results: After screening 16,042 patients, 7,411 patients were enrolled, of whom 668 were ChEI users and 1,336 were nonusers after 1:2 PSM. Compared with nonusers, ChEI users exhibited a significantly lower incidence of new-onset HF (hazard ratio [HR] 0.48; 95% confidence interval [CI] 0.34–0.68, p < 0.001) and cardiovascular death (HR 0.55; 95% CI 0.37–0.82, p = 0.003) but not of myocardial infarction (HR 1.09; 95% CI 0.52–1.62, p = 0.821) after 10-year follow-up. The preventive benefit of ChEI use compared with non-use (controls) was consistent across all exploratory subgroups without statistically significant treatment-by-subgroup interactions.